Constraining the thin disc initial mass function using galactic classical Cepheids - Mor, Rivay; Lemasle, Bertrand (Astronomy and astrophysics, 2017)
Context. The initial mass function (IMF) plays a crucial role in galaxy evolution and its implications on star formation theory make it a milestone for the next decade. It is in the intermediate and high mass ranges where the uncertainties of the IMF are larger. This is a major subject of debate and analysis both for Galactic and extragalactic science.Aims. Our goal is to constrain the IMF of the Galactic thin disc population using both Galactic classical Cepheids and Tycho-2 data.Methods. For the first time, the Besançon Galaxy Model (BGM) has been used to characterize the Galactic population of classical Cepheids. We modified the age configuration in the youngest populations of the BGM thin disc model to avoid artificial discontinuities in the age distribution of the simulated Cepheids. Three statistical methods, optimized for different mass ranges, have been developed and applied to search for the best IMF that fits the observations. This strategy enables us to quantify variations in the star formation history (SFH), the stellar density at Sun position and the thin disc radial scale length. A rigorous treatment of unresolved multiple stellar systems has been undertaken, adopting a spatial resolution according to the catalogues used. Results. For intermediate masses, our study favours a composite field-star IMF slope of α = 3.2 for the local thin disc, excluding flatter values, e.g. the Salpeter IMF (α = 2.35). Our findings are broadly consistent with previous results derived from Milky Way models. Moreover, a constant SFH is definitively excluded, the three statistical methods considered here show that it is inconsistent with the observational data. Conclusions. Using field stars and Galactic classical Cepheids, we found an IMF steeper than the canonical stellar IMF of associations and young clusters above 1 M⊙. This result is consistent with the predictions of the integrated Galactic IMF.